KARAKTERISTIK HABITAT GAJAH SUMATERA (Elephas maximus sumatranus) DI KAWASAN EKOSISTEM SEULAWAH KABUPATEN ACEH BESAR - Abdullah Abdullah; Asiah Asiah; Tomi Japisa (Universitas Syiah Kuala, 2012)
It has been done a research about 'Habitat Characteristics of Sumatran elephants (Elephas maximus sumatranus) in Seulawah Ecosystem region at regency of Aceh Besar', to see the characteristics of Seulawah unspoiled ecosystem, it is necessary to review what habitat factors that influence habitat selection by elephants in Sumatra. However, due to forest encroachment, the conditions of habitat at the site which is often used by elephants in the Seulawah ecosystem are changed, and including forest encroachment areas are extremely high. With the purpose to describing physically and biologically of the habitat characteristics of Sumatran elephants in the Seulawah ecosystem at Aceh Besar regency. Retrieval of data was held on 1-14 in December 2010. The parameters which used are the amount of feces found in habitat that is used by the Sumatran elephants in the Seulawah ecosystems at Aceh Besar regency. The data is collected on the track which located in the Seulawah ecosystem ata Aceh Besar regency and samples used are track with measure of 100x3m and then divided into 8 plots with distance between plots are 500m. The results showed that the Sumatran elephant selecting habitat unit with criteria (a) the slope of the ramps (0-20o), (b) close to the water source (0-250m), (c) close to the primary forest (0-500m); (d) the availability of minerals rare trees (3 trees), (e) low-elevation land (0-400m), (f) the availability of many feed (75%), (g) closing the canopy is very rare (0-25 %), (h) the availability of body scrub trees are rare (3 trees), and (i) the type of secondary forest. The results provide information about the factors that determine the selection of habitat by Sumatran elephants that can contribute in the management of suitable habitat for Sumatran elephants. This condition is expected to reduce elephant conflicts with the surrounding area.